Pengembangan dan Validasi Counselor Knowledge & Competences Post Disaster Inventory (CKCPDI) untuk Mengukur Kompetensi Konselor Pasca Bencana - Ifdil, Ifdil; Ghani, Faizah Abd (Universitas Negeri Padang, 2014)
There search objective was to develop and validation of the inventory; Counselor Knowledge & Competences Post Disaster Inventory (CKCPDI). The sample usedÂ 44Â kauselor in Indonesia. Validation constructs, person and reliability using RASCH Model analysis. The results from the item analysis showed that 56 items were tested usefully. The reliability coefficient Cronbach (KR-20) of CKCPDI was. 84. It concluded that the validity of CKCPDI was satisfying interm soft the measure of the Counselor Knowledge & Competences Post Disaster, and the construct of CKCPDI can be helpful and applicable for a counselor and ready used for the other research.